Exploration of Physics Concepts Based on Local Wisdom Kolecer Traditional Games - Mohammad Imam Sholahuddin; Setyo Admoko (PendIPA Journal of Science Education, 2021)
Teachers' perceptions in developing learning are needed to help students more easily capture information from the learning activities undertaken. One way that can be applied is by connecting learning materials with the local wisdom of the surrounding environment or commonly known as ethnoscience. Indonesia is a country rich in local culture in every region. Therefore, it is important for the nation's future generations to protect and preserve what already exists, for example by linking local culture to physics learning materials. The purpose of this study was to determine the potential for any physics concepts that exist in traditional kolecer games that can be applied to learning physics and everyday life. This type of research is the Narrative Review. Based on the research results, it was found that there was a potential application of physics concepts to local wisdom (ethnoscience) in the traditional "kolecer" game, these physics concepts were in the matter of equilibrium, pressure, Newton’s first and second law, work and energy, kinetic energy, and circular motion. It can be concluded that the application of local wisdom-based learning can help students easily grasp the material provided by the teacher and make learning more meaningful, especially on local wisdom of traditional kolecer games.